2020
DOI: 10.1128/jb.00058-20
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tat-Dependent Protein Secretion

Abstract: The transcription initiation signal elicited by the binding of ferric citrate to the outer membrane FecA protein is transmitted by the FecR protein across the cytoplasmic membrane to the FecI extracytoplasmic function (ECF) sigma factor. In this issue of Journal of Bacteriology, I. J. Passmore, J. M. Dow, F. Coll, J. Cuccui, et al. (J Bacteriol 202:e00541-19, 2020, https://doi.org/10.1128/JB.00541-19) report that the FecR sequence contains both the twin-arginine signal motif and the secretory (Sec) avoidance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…FecR is a single-spanning cytoplasmic membrane protein of type II topology, similar to other RseP substrates, and has been reported to be processed into several fragments in vivo ( 62 , 63 ). In addition, its N-terminal cytoplasmic region has been suggested to exhibit an activity (“pro-sigma” activity) that is required for the function of FecI ( 40 , 43 ). These facts led us to examine the possibility that FecR is cleaved by RseP to activate FecI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FecR is a single-spanning cytoplasmic membrane protein of type II topology, similar to other RseP substrates, and has been reported to be processed into several fragments in vivo ( 62 , 63 ). In addition, its N-terminal cytoplasmic region has been suggested to exhibit an activity (“pro-sigma” activity) that is required for the function of FecI ( 40 , 43 ). These facts led us to examine the possibility that FecR is cleaved by RseP to activate FecI.…”
Section: Resultsmentioning
confidence: 99%
“…The Fec proteins constitute the Fec system that mediates the uptake of ferric citrate by a cell ( 34 , 35 ). We demonstrated that FecR receives sequential processing at the membrane and that RseP plays an essential role in the activation of FecI, an alternative sigma factor dedicated to the transcription of the fec operon ( 36 , 37 , 38 , 39 ), through the regulated intramembrane cleavage of a periplasmically processed form of FecR, the regulator of the fec operon expression ( 40 , 41 , 42 ), which produces the N-terminal cytoplasmic tail fragment of FecR having a “pro-sigma” activity ( 40 , 43 ) as the last step in the sequential processing of FecR at the membrane. These results uncover the details of the FecR processing in the ferric citrate–induced TM signaling and a new physiological role of RseP in the iron uptake in response to the environmental conditions in E. coli .…”
mentioning
confidence: 99%
“…FecR is a single-spanning cytoplasmic membrane protein of type II topology, similar to other RseP substrates, and has been reported to be processed into several fragments in vivo (59, 60). In addition, its N-terminal cytoplasmic region has been suggested to exhibit an activity (“pro-sigma” activity) that is required for the function of FecI (40, 43). These facts led us to examine the possibility that FecR is cleaved by RseP to activate FecI.…”
Section: Resultsmentioning
confidence: 99%
“…The Fec proteins constitute the Fec system that mediates the uptake of ferric citrate by a cell (34, 35). We demonstrated that FecR receives sequential processing at the membrane and that RseP plays an essential role in the activation of FecI, an alternative sigma factor dedicated to the transcription of the fec operon (3639), through the regulated intramembrane cleavage of a periplasmically processed form of FecR, the regulator of the fec operon expression (4042), which produces the N-terminal cytoplasmic tail fragment of FecR having a “pro-sigma” activity (40, 43) as the last step in the sequential processing of FecR at the membrane. These results uncover the details of the FecR processing in the ferric citrate-induced transmembrane signaling and a new physiological role of RseP in the iron uptake in response to the environmental conditions in E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…It is used by all types of bacteria, as well as archaea, chloroplasts and plants mitochondria. In case of bacteria, Tat system exports proteins from cytoplasm across the inner cell membrane, whereas in chloroplasts, it is present in thylakoid membrane where it aids import of proteins from stroma [23,24]. That proteins have highly variability in different bacterial strains and are distributed into major types namely TatA, TatB and TatC.…”
Section: Srp Pathwaymentioning
confidence: 99%